Quality parameters, mineral profile and correlation of origin and physical-chemical parameters of Apis mellifera honey produced in southern Brazil - da Rosa, Franciéli Possa; Soares, Ledieli Belmonte; Resmim, Cássio Marques; Boff, Maíne Gavioli; de Moraes, Luana Passamani; Moreira, Felipe Teixeira; Brum, Clóvis Fernando Ben; dos Santos, Clarissa Obem; Tusi, Marcelo Marques (Ciência e Natura, 2021)
Beehive products, including honey, are valuable environmental indicators, as bees transport compounds in the environment by transferring them to the hive. Environmental pollutants can reduce the quality of honey and represent a risk for consumers. In this work, we characterised honey samples of Apis mellifera from different cities of the Rio Grande do Sul state (southern Brazil), sold without any inspection. A total of 23 honey samples were collected from 11 cities of Rio Grande do Sul. We carried out Lugol’s and Lund’s tests, analysed the electrical conductivity (EC), pH, and acidity of the honey samples, and determined their moisture, ash, reducing sugar, apparent sucrose, hydroxymethylfurfural (HMF), and diastase contents. Energy-dispersive X-ray fluorescence analysis was performed to determinate the mineral profile of the samples. Principal component analysis (PCA) was applied to the physicochemical data in order to differentiate the honey samples based on their origin. The analysis of the physicochemical parameters indicated that seven samples (30.4%) showed deviations from the reference values. PCA accounted for 90.03% of the variance with the first four principal component variables. Most samples were separated by the city of origin, supporting the possibility of using honey as an environmental marker.